Oral, physical, and behavioral aspects of patient with chromosome 47, XYY syndrome - Lisa Scheidt; Mariane Emi Sanabe; Michele Baffi Diniz (Wolters Kluwer Medknow Publications, 2015)
Chromosome 47, XYY syndrome is usually diagnosed late. Some of the clinical characteristics of XYY syndrome may be perceptible in dental care. The slow development of cognitive and motor activities and tall stature is common in XYY patients. The aim of this article was to relate the oral, physical, and behavioral aspects of a 6-year-old patient with the chromosome 47, XYY syndrome, diagnosed by means of karyotyping. The patient presented motor difficulty, which led to a fall and traumatism in the anterior region. In the radiography, agenesia of the permanent maxillary lateral incisors, presence of taurodontism in the primary molars, and macrodontia of the maxillary central incisors and permanent molars could be observed. Once the diagnosis was made, it was possible to understand his difficulty at school, and make available appropriate monitoring by a suitable multidisciplinary team to stimulate, control, and minimize the day-to-day difficulties found by patients with this syndrome.